Kin. Season 1 [videorecording (DVD)] - Cox, Charlie, 1982-; Dunne, Clare; Gillen, Aidan, 1968-; Scanlan, Emmett J.; Kennedy, Maria Doyle; Keeley, Sam, 1990-; Seky, Yasmin; Hinds, Ciarán, 1953- (AMC Studios, 2022)
A boy is killed and his family embark on a gangland war with an international cartel, a war that is impossible to win. But the Kinsellas have something the cartel does not: the unbreakable bonds of blood and family.